التحول الرقمي كاستراتيجية للتنويع الاقتصادي دراسة حالة : المملكة العربية السعودية - جرمون سعاد (جامعة الوادي University Of Eloued, 2024)
تأثرت اقتصادات دول المصدرة للنفط خاصة السعودية سلبا نتيجة التقلبات في أسعار النفط العالمية ، نظراً لأن القطاع النفطي هو المصدر الرئيسي للدخل من الناتج المحلي الإجمالي للسعودية ، دفع التراجع الحالي لأسعار النفط إلى المطالبة بمراجعة جوهرية تستهدف التنويع الاقتصادي، ونظرا لما يشهد العالم في هذه الآونة تتطور التكنولوجيا وتحول الأنشطة الاقتصادية التقليدية إلى أنشطة اقتصادية رقمية ، حيث شرعت المملكة العربية السعودية في تنمية الاقتصاد الرقمي كأحد أهم ممكنات تعزيز قدرات القطاعات غير النفطية والتي تسهم في تنمية وتنويع الاقتصاد في اطار برنامج التحول الوطني في ظل "رؤية السعودية 2030 " ، سنحاول من خلال هذه الورقة البحثية تسليط الضوء على تجربة المملكة العربية السعودية في التحول الرقمي كاستراتيجية للتنويع الاقتصادي . The economies .of the oil-exporting countries, especially Saudi Arabia, have been negatively affected as a result of fluctuations in global oil prices, given that the oil sector is the main source of income from the gross domestic product of Saudi Arabia. Technology and the transformation of traditional economic activities into digital economic activities, as the Kingdom of Saudi Arabia has embarked on the development of the digital economy as one of the most important capabilities to enhance the capabilities of non-oil sectors that contribute to the development and diversification of the economy within the framework of the national transformation program under the "Saudi Vision 2030", we will try through this The research paper sheds light on the experience of the Kingdom of Saudi Arabia in digital transformation as a strategy for economic diversification.
Digital transformation as a strategy for economic diversification Case study: Saudi Arabia
Keywords: التنويع الاقتصادي; التحول الرقمي; رؤية 2030; Economic diversification; digital transformation; Vision 2030